Population estimate and morphometry of ovarian preantral follicles from three recently recognized squirrel monkey species: a comparative study. Issue 3 (23rd May 2017) - Lopes, Gerson P.; Santos, Regiane R.; Almeida, Débora V.; Brito, Adriel B.; Queiroz, Helder L.; Domingues, Sheyla F. S.
Summary: We describe morphological and morphometrical characteristics of preantral ovarian follicles from three recently recognized Saimiri species: S. macrodon, S. cassiquiarensis and S. vanzolinii ; the last one a threatened species. Ovaries from four adult monkeys were evaluated: one pair from a pregnant S. macrodon, two ovarian pairs from S. cassiquiarensis females (one of them pregnant), and one left ovary from a senile S. vanzolinii, applying classical histology. Follicular preantral population was quantified and morphology and morphometry of primordial, primary and secondary follicles were evaluated. Follicular preantral population varied among species, being 347, 153 in the ovaries of the S. macrodon, 270, 342 and 278, 376 in the ovaries of both adult non-pregnant and pregnant S. cassiquiarensis females, and 28, 149 in the ovary from a senile S. vanzolinii. Most follicles were at primordial or transition stages, except for the senile S. vanzolinii female, which presented the lowest percentages of primordial and transition follicles when compared with primary and secondary ones. Most preantral follicles (>70%) were morphologically normal in the ovaries from all studied S. macrodon and S. cassiquiarensis females, but the ovary of the senile S. vanzolinii female presented a significant decrease in the percentage of normal follicles (primordial: 61%, transition: 52%, primary: 54%, and secondary: 48%). In general, follicular diameter increased significantly from primordial to transition, and subsequently from primary to secondary follicles.